Pemanfaatan Limbah Pouch Kopi sebagai Bahan Baku Produk Ramah Lingkungan: (Studi Kasus pada Demibumi dan Brookland Coffee) - Dinda Kusuma Gunawan; Evelyn Veronica; Karren Gracia (Jurnal Riset dan Inovasi Manajemen, 2025)
Based on data from the United States Department of Agriculture (USDA), global coffee production reached 170 million bags per 60 kg of coffee during the 2022/2023 period. Indonesia is noted as one of the largest coffee-producing countries in the world in 2023. The plastic packaging waste from coffee shops is increasing, posing a potential threat to environmental sustainability, such as soil and water pollution. According to Bizhare Contributor in 2023, the Food and Beverage industry in Indonesia has already reduced plastic waste, but there are still plastic packaging, particularly for coffee beans, that cannot be replaced with environmentally friendly materials. From this, the problem of this research is "How is plastic pouch waste sorted in coffee shops and how is it processed to become selling goods?". This research aims to determine the sorting of coffee pouch plastic waste in coffee shops and the processing process to make it into selling goods. The data collected through interviews shows that from the various coffee shops that have mushroomed in Jakarta, there are also coffee shops that care about the environment by sorting plastic waste. This coffee shop, namely Brookland Coffee, participates in donating coffee pouch waste to Demibumi, the process of making coffee pouches Environmentally friendly by Demibumi starts with collecting coffee pouch waste, cutting off the top, and sewing the outside with patchwork, then attaching it with adhesive so it can be folded. The conclusions obtained by DemiBumi prove that concrete action can be taken to overcome this problem. The main conclusion from this issue is that even though it is a big challenge, efforts to manage plastic waste can be successful and have a positive impact on the environment as long as it is carried out carefully by the community, such as through education, awareness campaigns, and the development of innovative solutions to reduce the use of single-use plastics can be steps. significant step.